IMPACT OF CARBO-GASEOUS SALINE WATERS REGISTERED BY SOILS - Cornu S.; Negrel P.; Brach M. (My University, 2001)
The impact of carbo-gazeous saline spring waters, rich in Ca, Fe, As and P and chemically stable through time, on the chemistry (major and trace elements) and mineralogy of soils developed from anatexite is presented. The soils developed beyond the influence of the spring are typical of a granite pedogenesis on a granitic bedrock with Ca loss, Si, Al and K conservation. The soils influenced by the springs are enriched in Ca and Fe, respectively, precipitated as carbonates and oxides. In such soils, the presence of two Ca-enrichment peaks may be explained by the occurrence of two distinct precipitation mechanisms for the carbonates: (1) related to degassing of the carbo-gaseous waters upon emergence at the surface, and (2) in the water-unsaturated zone, related to capillary rise and evaporation processes. The precipitation of iron oxides is related to a change in the redox potential of the mineral waters, following their emergence at the surface.The simultaneous association of As+P with Fe, as evidenced by principal components analysis and in the patterns in concentrations vs. depth observed in soils, can be explained by adsorption and/or coprecipitation of As and P during iron-oxide formation, while The As and P enrichments and the carbonate formation are independent.The extent of the spring influence was studied: the soil enrichments in Ca and, particularly, Fe sharply decrease with increasing distance from the spring on a metric scale.
Keywords: CARBO-GASEOUS SPRING; SOILS; CALCITE; IRON OXIDE; ARSENIC; PHOSPHATE